MINIATURIZATION OF A PLANAR STRIP-SHAPED MONOPOLE ANTENNA FOR WLAN APPLICATION - FADHEL, YASSER A.; ATAŞ, MUSA; ABDULHAKIM, REVINK M. (Journal of Duhok University, 2017)
Recently the demand for compact size devices has been increased whether being used for sensor networks, smart phones, smart watches or RFID tags etc. One of the most important parts of these systems is its antenna which facing a big challenge of having a low profile that meets the required size of these wireless communication devices. This paper presents a design of a simple planar strip monopole antenna for WLAN application. Miniaturization has been performed on this antenna via two different techniques. Firstly corrugations were added to both side edges of the radiating strip that reduced the size with 10.7% of the original size. Secondly the radiating strip has been meandered to increase the size reduction to about 14.28%. Both simulation and measured results shown that meandering technique was more efficient in miniaturizing the size of the designed antenna due to forcing the current to follow a meandered path that rise up with shorter height.